The Magnitude and Directions of the Associations between Early Life Factors and Metabolic Syndrome Differ across Geographical Locations among Migrant and Non-Migrant Ghanaians—The RODAM Study - Thijs G. W. van der Heijden (MDPI AG, 2021)
Background: Early-life factors (ELFs) such as childhood nutrition and childhood socio-economic status could be the drivers of the increase in metabolic syndrome (MetSyn) among African populations, but data are lacking. This study evaluated whether markers of childhood nutritional status and childhood socio-economic status were associated with MetSyn in adulthood among migrant Ghanaians living in Europe and non-migrant Ghanaians living in Ghana. Methods: Data from the Research on Obesity and Diabetes among African Migrants (RODAM) study, involving 2008 migrants and 2320 non-migrants aged ≥25 years, were analysed for this study. We used leg-length to height ratio (LHR), which is an anthropometric marker of childhood nutritional status, and parental education, which is a marker of childhood socio-economic status, as proxies. Adjusted odds ratios (AOR) and 95% confidence intervals (95% CI) were calculated by logistic regression with adjustments for demographic and lifestyle factors. Results: Parental education was higher among Ghanaians in Europe than among residents in rural and urban Ghana. The prevalence of MetSyn was 18.5%, 27.7% and 33.5% for rural, urban, and migrant residents, respectively. LHR was inversely associated with MetSyn among migrants. Compared with high paternal education, individuals with low paternal education had lower odds of MetSyn in migrants (AOR 0.71 95% CI 0.54–0.94). In contrast, compared with high maternal education, individuals with intermediate maternal education had higher odds of MetSyn in urban Ghanaians (AOR 4.53 95% CI 1.50–3.74). No associations were found among rural Ghanaians. Conclusion: The magnitude and direction of the associations between ELFs and MetSyn differ across geographical locations. Intermediate maternal education was positively associated with MetSyn among urban Ghanaians, while LHR and low paternal education were inversely associated with MetSyn among migrant Ghanaians. Further research into the interplay of genetics, environment and behaviour is needed to elucidate the underlying pathological mechanisms of MetSyn amongst migrants.